Traditional Belarusian wooden calendar from Sluck County - Butov, Ilya S.; Skvarcheuski, Dzmitry V. (Journal of the Belarusian State University. History, 2021)
Carved wooden calendars were known to many peoples from the Middle Ages to the beginning of the 20th century. For example, the Scandinavian ones are well enough studied, but about the existence of such calendars among Belarusians wasn’t known for a long time. The Russian Museum of Ethnography has a carved calendar from the Sluck County. Today it is the only such Belarusian artifact. The article presents a description of a carved wooden calendar from the Čudzin Village, Sluck County. A brief overview of other calendars of a similar type is shown. The prerequisites for the formation and distribution of such artifacts on the territory of Belarus were studied. The article discusses the sign system used to designate holidays and working periods, which correlate with the calendar tradition of the region. Based on the data obtained, the authors draw conclusion about the local origin of the calendar.
Keywords: carved wooden calendar; folk calendar; feast days; graphic sign system